ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN PETANI SALAK BEREGISTER DI GAPOKTAN NGUDI LUHUR DESA KALIURANG KECAMATAN SRUMBUNG KABUPATEN MAGELANG - Sidiq Purwidiyanto; Ari Astuti; Wahyu Setya Ratri (JURNAL ILMIAH AGRITAS, 2022)
This study aims to determine the farm income of Nglumut salak farmers and the welfare level of salak farmers in the Ngudi Luhur Gapoktan, Kaliurang Village. Ngudi Luhur Gapoktan has penetrated the marketing of salak to foreign countries. One of the requirements for salak gardens must be registered according to GAP (Good Agriculture Practice) and SOP (Standard Operating Procedure) with prime certification land. This research method uses a quantitative descriptive method. The number of respondents using the Slovin determination method. The number of respondents in this study was 41 registered farmers of Salak Nglumut. The time of the study was carried out in March - April 2021. The results showed that the income of salak farmers was financially feasible after being tested, the NPV showed > 0. The results of the study related to the level of farmers' welfare using the GSR (Good Service Ratio) criteria, it is known that food expenditure is 33.4% and non-food expenditure is 66.6%, indicating that 68% of farmers are prosperous, 17% of farmers are low-income and 15% are prosperous farmers high level.